Preclinical and pilot clinical evaluation of novel dual-modality pet/fluorescence probes targeting FAP for accurate tumor margin delineation. - Zhao, Liang; Pang, Yizhen; Xu, Daqiang; Chen, Jianhao; Yu, Shan; Ruan, Dan; Yu, Lingyu; Wu, Zhenyu; Su, Guoqiang; Wu, Hua; Ai, Lin; Sun, Long; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2026)
Purpose: Accurate delineation of tumor margins and maximal safe resection are critical for successful curative oncologic surgery. However, fibroblast activation protein (FAP)-targeted probes suitable for fluorescence imaging remain limited. Here, we developed novel FAP-targeted fluorescent probes to accurately delineate tumor margins and enable rapid intraoperative identification of tumor boundaries in resected specimens. Methods: DOTA chelator for radiolabelling with gallium-68 was incorporated into dual-modality FAP-targeted probes synthesised by conjugating FAP-2286 and 3BP-3940 with the near-infrared (NIR) fluorophore IRDye800CW. These probes were evaluated both in vitro and in vivo using HEK293T-FAP cells stably expressing FAP and xenograft mouse models. Positron emission tomography (PET) and (NIR-II) fluorescence imaging assessed the specificity and ability of probes to delineate tumor margins. For clinical validation, resected lung tissue was incubated ex vivo with the probes. Tumor regions and margins were identified using fluorescence imaging and subsequently validated by haematoxylin and eosin (H&E) staining and FAP immunohistochemistry. Results: Both IRDye800CW-FAP-2286 and IRDye800CW-3BP-3940 exhibited high affinity for FAP-positive cells in vitro. PET imaging revealed high tumor specificity for both probes in vivo. In vivo and ex vivo NIR-II fluorescence imaging enabled accurate visualisation of tumor margins, with IRDye800CW-3BP-3940 exhibiting superior performance compared with IRDye800CW-FAP-2286. In the clinical specimen, IRDye800CW-3BP-3940 successfully delineated tumor regions with strong concordance to histopathological findings. Conclusion: We developed and validated a novel dual-modality molecular probe, IRDye800CW-3BP-3940, which integrated PET and NIR fluorescence imaging capabilities. This probe enabled highly specific detection of FAP-positive tumors and precise delineation of tumor margins in resected specimens.